Effect of gelatinized flour fraction on thermal and rheological properties of wheat-based dough and bread - Carrillo-Navas, H. (J Food Sci Technol, 2016)
This work considered gelatinized wheat flour fraction with properties similar to hydrocolloid to enhance the strength of dough network by improving water retention and rheological characteristics. The gelatinized (90 °C) fraction of the wheat flour was incorporated in the dough formulation at different levels (5, 10, and 20% w/w). The effects of the gelatinized flour (GF) fraction on the dough rheology and thermal properties were studied. The incorporation of GF induced a moderate increase of dough viscoelasticity and reduced the freezing and melting enthalpies. On the other hand, the changes in bread textural properties brought by incorporation of GF were insignificant, indicating that the gelatinized fraction acted as a binder that enhanced water trapping in the structure. SEM images showed a more heterogeneous crumb microstructure (e.g., gas cells, porous, etc.) bread prepared using GF. Drying kinetics obtained from TGA indicated that the water diffusivity decreased with the incorporation of GF, which suggested that the bread had a compact microstructure.